Rancang Bangun Aplikasi CRM Fleet Management System dengan Algoritma Searching Sequential - Fahrul Dwi Affandi; Sabar Rudiarto (Fakultas Ilmu Komputer, 2018)
Shipping company is companies that provide services in collection, management, warehousing and delivery of goods or commonly called forwarding agents. Shipping goods is the process of moving goods from one place to another. One of the tools used by the shipping company is transportation. Wich is the reason why people or companies need shipping service is a means of transpotation that supports people or companies themselves is very limited. Therefore, the services of other parties are needed to help deliver goods. Because this delivery service requires a lot of drivers, the shipping company needs driver data storage media that is owned while searching for a driver who is delivering and not so that the shipment of goods is in accordance with the given schedule and able to be on time. There areseveral algorithms that can be used, one of which is sequential search, which is a basic and easy algorithm for searching where the process looks for data in a 1-dimensional array that will be traced in all elements of the array element to the end and the data sought does not need to be sorted first fist. In this research, the data search system uses the sewuential search method to be able to recommend the driver and fleet available for delivery.